PEMBERDAYAAN KOPERASI MELALUI TRANSFORMASI TATA KELOLA DAN ADMINISTRASI DIGITAL BERBASIS GOOGLE WORKSPACE - Daris Purba; Asih Purwana Sari; Elli Widia (Bajang Institute, 2025)
Cooperatives face significant challenges in the digital era, particularly in relation to governance and administrative systems that remain largely conventional. This community service program aims to empower the Employee Consumer Cooperative of PT Rubycon Indonesia Sejahtera by transforming governance practices and digitalizing administrative systems. The program employs a participatory, empowerment-oriented approach, in which the partner was not provided with a ready-made application but was instead trained to develop its own digital system using the Google Workspace platform. The implementation stages included socialization, managerial and technical training, and intensive mentoring. The results demonstrate tangible improvements in cooperative governance and performance. The cooperative successfully developed Standard Operating Procedures (SOPs) and strengthened its governance structure, leading to increased operational efficiency. As an initial measurable outcome, the cooperative reported an increase in revenue following the implementation of improved governance practices. This empowerment-based approach proved effective in fostering a strong sense of ownership and ensuring system sustainability, as the digital system was independently developed and managed by the cooperative